Transformation coopérative, travail de négociation et communs : les interactions du matériel et de l’idéel - Yvan Renou; Hervé Charmettant (Développement Durable et Territoires)
In this article, we propose to apprehend cooperative transformation as an institutional work relative to negotiation, as a collective effort with a strong reflexive content of redefinition of management situations and actors’ identities. The sustainability of the established Labor-Managed Firms can therefore be envisaged through the degree of coherence – built and reactivated in successive negotiations – of the resource system consisting of common assets, a common good (the politico-economic project) and a common principle (democratic action). The dialectical tensions between the material and ideal dimensions of this system are analyzed through the study of the transformation of six enterprises in the Auvergne Rhône-Alpes region.